Improved phase-change properties of Sn–Zn–Sb alloys with a two-step crystallization process for multi-level data storage applications. Issue 13 (September 2019) - Zhang, Yawen; Wang, Guoxiang; Liu, Fen; Wang, Rongping; Chen, Yimin; Shen, Xiang; Lu, Yegang
Abstract: We investigated Te-free ZnSb films for the potential applications in multi-level data storage. It was found that, the films could exhibit three phases during crystallization process, e.g., high amorphous phase, intermediate metastable ZnSb phase, and low stable ZnSb phase. However, the formation of the voids in the metastable ZnSb phase, high crystallization temperature and large amorphous resistance have an influence on the structure stability and SET power consumption during the repeated switching process. Interestingly, doping of Sn with a concentration of 11.1 at% into ZnSb can prevent the growth of metastable ZnSb grains, and different crystals like SnSb and ZnSnSb2 can be precipitated out during heat treatment, but the two-step crystallization process is kept unchanged. Moreover, the chemical environment of Sn in Zn–Sb studied by X-ray photoelectron spectroscopy indicates the formation of the large number of Sn–Sb and Sn–Zn bonds, which in turn reduces the crystallization temperature, lowers crystallization activation energy as well as decreases the amorphous resistance. The in situ transmission electron microscopy measurements on the optimized (ZnSb)88.9 Sn11.1 composition confirms a two-step phase transition process from amorphous to rhombohedral SnSb crystals first, and then to the stable tetragonal ZnSb2 Sn crystals. These excellent properties make Zn–Sb–Sn materials useful as a phase-change layer in low-power and high-density memory.